Determination of Optimal Conditions for Catalytic Hydrogenation of Oil Sludge (Atasu-Alashankou) - Tyanakh, S.; Baikenov, M.I.; Ma, Feng-Yun; Fomin, V.N.; Baikenova, G.G.; Ashimhanov, A.S.; Seitzhan, R.S. (Eurasian Journal of Chemistry, 2023)
The optimal conditions of catalytic hydrogenation of oil sludge (Atasu-Alashankou) and the change in the kinematic viscosity of the fraction to 350℃ from the studied factors using the method of probabilistic-deterministic planning were experimentally determined. During the hydrogenation process of oil sludge, the maximum total yield of light fractions reached 62.1 %, and the kinematic viscosity decreased from 2.2 to 1.2 mm2/s. It was established the initial hydrogen pressure and the amount of added nanocatalyst microsilicate with cobalt (catalyst 1) have the greatest influence on the yield of the middle fraction from oil sludge under experimental conditions. It was shown that catalyst 1 increases the yield of diesel fraction com-ponents during the hydrogenation process of oil sludge. For the first time, we established the individual and group chemical composition of the fraction up to 350℃ before and after processing. The use of nanocatalyst 1 in amounts of 1.2–1.5 % led to an increase in the yield of the fraction up to 350℃ and diesel fraction compo-nents. This is due to the yield of paraffinic hydrocarbons increasing from 57.6 (initial fraction) to 80.7 %, as well as a decrease in aromatic hydrocarbons from 14.1 to 12.9 % and polycyclic aromatic hydrocarbons from 9.56 to 4.3 %.
Keywords: optimization; oil sludge; catalyst; microsilicate; cobalt; nickel; viscosity; hydrogenation; optimiza-tion; correlation